Securitization of Cyber Threats to the Indonesian Government:A Study of Cyber Defense Strategy - Wibowo, Sarwo Edi; Hartono, Ari; Kiswanto, Hendri; Primawanti, Henike; Louerens, Jafirman Torang Avery (Universitas Komputer Indonesia, 2024)
The research aims to analyze the cyber threats faced by Indonesia and the issues in them. To achieve this goal, this research explores the Indonesian government's view of cyber security as a non-traditional security threat and the Indonesian government's approach to dealing with cyber threats. It examines the extent to which securitization is carried out by various actors representing the Indonesian government. This research uses a qualitative method with an analytical descriptive form that utilizes direct and indirect sources such as interviews with several informants, literature studies, and documentation studies. This research used a non-traditional security approach, including the securitization theory related to cybersecurity. The finding of this paper suggests that The Ministry of Defense of Indonesia as a state institution did securitization that focuses on the idea of military involvement in securing cyberspace by increasing the current level of cyber technology has been accompanied by an increase in the vulnerability of cybercrime and cyber-attacks both in quality and quantity. The Ministry of Defense formed COC (Cyber Operation Center) as the frontline. It formed the cyber army to strengthen the defense and attack the cyber threat in the Ministry of Defense’s area. Keywords — Cyber Security, Cyber Threats, Defense Strategy, Ministry of Defense, Securitization